Cost-benefit analysis of VKA versus NOAC treatment in German patients with atrial fibrillation utilizing patient self-testing - Roland Diel; Niklas Lampenius (Journal of Health Economics and Outcomes Research)
# Background Clinical complications of long-term anticoagulation in patients with atrial fibrillation cause significant morbidity and have a substantial economic impact on the healthcare system.